2013
DOI: 10.1371/journal.pone.0060839
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Tanscriptomic Analysis on Giant Freshwater Prawns

Abstract: Gene discovery in the Malaysian giant freshwater prawn (Macrobrachium rosenbergii) has been limited to small scale data collection, despite great interest in various research fields related to the commercial significance of this species. Next generation sequencing technologies that have been developed recently and enabled whole transcriptome sequencing (RNA-seq), have allowed generation of large scale functional genomics data sets in a shorter time than was previously possible. Using this technology, transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
(75 reference statements)
1
23
2
Order By: Relevance
“…For example, ~3 times more contigs were recovered from Hyas araneus than originally described (Harms et al , 2013), likely due to Illumina, rather than Roche 454, data becoming available for this species. However, contig numbers for Portunus trituberculatus (123,015 vs. 94,511) and Macrobrachium rosenbergii (95,321 vs. 102,230) were similar relative to previous transcriptome assemblies, likely because they were generated from the same sequence data with comparable assembly methods (Lv et al , 2013; Mohd-Shamsudin et al , 2013). Lastly, to the best of our knowledge, this is the first report of a gill transcriptome for Carcinus aestuarii , which possessed 48,355 contigs and a similar annotation rate to that of C. sapidus (Table 1).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, ~3 times more contigs were recovered from Hyas araneus than originally described (Harms et al , 2013), likely due to Illumina, rather than Roche 454, data becoming available for this species. However, contig numbers for Portunus trituberculatus (123,015 vs. 94,511) and Macrobrachium rosenbergii (95,321 vs. 102,230) were similar relative to previous transcriptome assemblies, likely because they were generated from the same sequence data with comparable assembly methods (Lv et al , 2013; Mohd-Shamsudin et al , 2013). Lastly, to the best of our knowledge, this is the first report of a gill transcriptome for Carcinus aestuarii , which possessed 48,355 contigs and a similar annotation rate to that of C. sapidus (Table 1).…”
Section: Resultsmentioning
confidence: 79%
“…Specifically, the four gill data sets were from the crabs Portunus trituberculatus (Lv et al , 2013), Hyas araneus (Harms et al , 2014; Harms et al , 2013), and Carcinus aestuarii (Romiguier et al , 2014), and the giant river prawn Macrobrachium rosenbergii (Mohd-Shamsudin et al , 2013). …”
Section: Methodsmentioning
confidence: 99%
“…However, at present the genomic data available for the Caridea are rather scarce. No Caridean genome has been sequenced and only few transcriptome datasets are available for two Palaemonidae species, M. rosenbergii (Mohd-Shamsudin et al 2013) and M. nipponense (Ma et al 2012;Jin et al 2013). The most documented type of genomic data remains b Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The T7 primers were designed by incorporating the region 5′‐TAA TAC GAC TCA CTA TAG GG‐3′ into both the forward and reverse primers of Mr MSTN and GFP. The primers for the cogene regulation study were designed using the template of respective unigenes that are identified from the transcriptome data of M. rosenbergii (Mohd‐Shamsudin et al, ). Elongation factor – 1 (EF‐1) was used as a control for quantitative polymerase chain reaction, and the primer was designed based on an expressed sequence tags similar to the EF‐1‐alpha from M. rosenbergii (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%